2022
DOI: 10.1039/d2ra01049f
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic CoCu-ZIF material for efficient visible light photocatalytic fuel denitrification

Abstract: Effective design of photocatalysts is an effective method to improve the separation of photogenerated carriers, which improves the photocatalytic performance of photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…The Raman spectra of powder samples jn-01 and jn-04 are presented in Figure 4 a,b. In the Raman spectra, peaks are seen that match up with the peaks of the corresponding ZIFs, which is in good agreement with data from the literature [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. As seen in Figure 4 a, sample jn-01 shows the vibrational band characteristics of ZIF-8 (ZIF-L) that have been previously published in various papers [ 52 , 56 ].…”
Section: Resultssupporting
confidence: 90%
“…The Raman spectra of powder samples jn-01 and jn-04 are presented in Figure 4 a,b. In the Raman spectra, peaks are seen that match up with the peaks of the corresponding ZIFs, which is in good agreement with data from the literature [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. As seen in Figure 4 a, sample jn-01 shows the vibrational band characteristics of ZIF-8 (ZIF-L) that have been previously published in various papers [ 52 , 56 ].…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure 1, both samples were having the main peaks which appeared at 2θ of 7.3°, 10.4°, 12.7°, 14.7°, 16.41°, and 18.01° and could be attributed to the (011), ( 002), ( 112), ( 022), (013), and (222). These peaks have been recognized as distinctive features of ZIF-67, consistent with findings from various studies that have investigated the synthesis of ZIF-67 [21][22][23]. The incorporation of Cu 2+ did not yield a significant change on the materials diffraction pattern, as evidenced by the similar XRD spectra of Co/Cu ZIF-67 with the single-metal ZIF-67.…”
Section: Resultssupporting
confidence: 87%
“…Another explanation suggests that the exchange of metal ions in bimetallic MOFs provides more free charge carriers and increased interlayer distance, subsequently enhancing the conductivity [13,31]. Furthermore, Lu et al (2022) reported a significant increase in Brunauer-Emmett-Teller surface area and pore volume in Co/Cu-based MOFs, reaching 1834.71 m²/g and 0.788 cm³/g, respectively [23]. Therefore, the increase in peak current compared to single-metal ZIF-67 obtained in this study is plausible.…”
Section: Figure 1 Xrd Spectra Obtained From the Characterization Of Z...mentioning
confidence: 99%
“…The Raman peaks at 477 and 684 cm −1 are typically observed with ZIF-67, whereby 477 cm −1 is attributed to the Co-N bond and the vibration mode at 684 cm −1 is assigned to the 2methylimidazolate ligand. 21 The Raman signals positioned at 198, 524 and 616 cm −1 are all assigned to F 2g and the signal at 477 cm −1 and the strongest signal at 684 cm −1 are assigned to A 1 and E g mode respectively. 22,23 FTIR spectra presented in Fig.…”
Section: Papermentioning
confidence: 96%